MULTILINGUALISM, IDENTITY, AND EDUCATIONAL PRIVILEGE: A SOCIOLINGUISTIC ANALYSIS OF YOUNG EFL LEARNERS IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
This paper critically examines the sociolinguistic realities of young multilingual EFL learners within a private-school context in Uzbekistan. Drawing on sociolinguistic theories related to multilingualism, identity construction, language ideology, linguistic capital, and educational privilege, the study explores how learners aged 10–12 negotiate Uzbek, Russian, and English across diverse social and academic domains. The paper argues that English in this context functions not only as a foreign language for academic instruction, but also as a socially valued resource associated with globalization, educational mobility, intelligence, and institutional prestige. Particular attention is given to the influence of multilingualism, gendered interactional norms, code-switching practices, standard language ideology, and future-oriented educational expectations on learners’ participation and communicative behavior. Furthermore, the paper discusses how these sociolinguistic factors shape pedagogical decisions, classroom interaction, and assessment practices in EFL instruction. The analysis emphasizes the importance of sociolinguistically informed pedagogy that recognizes multilingual learners’ linguistic repertoires, promotes inclusive classroom practices, challenges discriminatory language ideologies, and prepares learners for authentic global communication beyond native-speaker norms. Ultimately, the paper highlights the role of TESOL professionals as socially responsive educators and advocates capable of addressing the complex relationship between language, identity, and educational inequality within multilingual learning environments.